Measuring Resilience and Risk Factors for the Psychosocial Well-being of Aboriginal and Torres Strait Islander Boarding School Students: Pilot Baseline Study Results - Redman-MacLaren, Michelle Louise; Klieve, Helen; Mccalman, Janya; Russo, Sandra; Rutherford, Katrina; Wenitong, Mark; Bainbridge, Roxanne Gwendalyn (Frontiers in Education, 2017)
Introduction Education provides a key pathway to economic opportunities, health and wellbeing. Yet limited or no locally available secondary schooling in remote Queensland Aboriginal and Torres Strait Islander communities requires more than 500 Indigenous students to transition to boarding schools. We report baseline quantitative data from the pilot phase (2016) of a 5-year study to explore a multicomponent mentoring approach to increase resilience and wellbeing for these students. Materials and Methods An interrupted time series design is being applied to evaluate levels of change in students’ resilience and wellbeing. Surveys were collaboratively developed, with questions adapted from the Child and Youth Resilience Measure (CYRM-28), Kessler Psychological Distress Scale (K5), and questions which identified upstream risk factors for self-harm (De Leo, Sveticic et al. 2011). They were completed by 94 students from five randomly selected schools (2 primary and 3 secondary) and one remote community. Results Pre-transition, most primary school students reported high levels of resilience, but only a third reported moderate - high levels of psychological wellbeing. Secondary students attending a boarding school reported lower scores on resilience and psychosocial wellbeing measures. Students who transitioned back to community after being from boarding school reported a lower sense of connection to peers and family, and they reported even lower resilience and psychosocial wellbeing scores. Learning Outcomes Students have many strengths and can be adaptable, but their levels of resilience and psychosocial wellbeing are affected by the schooling transitions they are required to navigate. The findings are informing the development of intervention strategies to enhance student resilience and wellbeing.